A Fuzzy Logic Based DSTATCOM for Diesel Generation System for Load Compensation - JACOB PRABHAKAR BUSI; SRINIVASARAO YELAVARTHI (Institute of Advanced Engineering and Science, 2015)
This paper proposes the concept of distributed static compensator for compensation of harmonics, unbalances and reactive powers. The main aim of this diesel electrical generator is to generate electrical power and transfer to the distribution point. The main problems occurred in this distribution systems are voltage distributions, interruptions and variations in distribution system also called as power quality problems. The FACTS controllers are classified into different types based on improvement of power quality. These facts devices are classified based on their construction and connection to the line i.e. called as series and shunt converters. This paper also concentrate on the concept of fuzzy logic controller for getting better performance as compared with the previous conventional controllers. Basically, the fuzzy controller has the advantage of low steady state error and also it reduces the These experimental diagrams are verified in Matlab/Simulink and the results are verified for both PI and Fuzzy controllers.